PILKADA LANGSUNG DAN REKONSTRUKSI DEMOKRASI INDONESIA - Dzunuwanus Ghulam Manar (JIIP: Jurnal Ilmiah Ilmu Pemerintahan, 2016)
Many people assume that success of the direct local leaders election (pilkada langsung) could be an indicator of successfull democracy in the local level. However, that early assumption need to be corrected since direct local leaders election is only a small process within local democracy. After elected as local leaders, it is important to assess their promises, performances, process, and output as manifestation of their political promises.